أثر القيادة الجديرة بالثقة على الانطمار الوظيفي: دراسة حالة شركة سرت لإنتاج وتصنيع النفط والغاز بمدينة البريقة. - الصويعي د. هند خليفة; عبدالسيد د. سهام إبراهيم (Dirasat in Economics and Business, 2022)
This study aimed to identify the level of practice of the dimen-sions of trustworthy leadership from the point of view of emplo-yees in the human resources management in the Sirte comp-any, as well as knowing the level of job embeddedness emplo-yees, and also knowing the im-pact of trustworthy leadership on the job embeddedness emplo-yees in the human resources management in Sirte company, and to achieve Objectives of the study The two researchers devel-oped a questionnaire based on some previous studies that inclu-ded (32) items to collect primary data from the study sample consisting of (155) individuals. (SPSS), and the results of the study indicated that the general level of trustworthy leadership from the employees’ point of view was high, and the study revealed that the general level of job embeddedness among the research sample was also high, and the showed that there is a statistically significant effect of the dimensions of leadership on job embeddedness , the study put forward a set of recommendat-ions that may contribute to the promotion of trustworthy leader-ship practices and increase the level job embeddedness The co-mpany isunderstudy.